FRI0452 Predictors of Pulmonary Arterial Hypertension in 79 Patients with Mixed Connective Tissue Disease. (9th June 2015) - Felis-Giemza, A.; Kontny, E.; Haładyj, E.N.; Rowinska-Osuch, A.; Walkiewicz-Pielaszek, K.; Czuszynska, Z.; Zdrojewski, Z.; Paradowska-Gorycka, A.; Olesinska, M.
Abstract : Background: Pulmonary arterial hypertension (PAH) is the predominant cause of morbidity and mortality in mixed connective tissue disease (MCTD). PAH is characterized by the thickening of the small arteries, arterioles of the lungs, development of plexiform lesions, arteritis and intima media hypertrophy. The incidence of PAH in MCTD is estimated between 20% and 30% 1-3 . Objectives: The aim of the study was to estimate the prevalence of PAH in a cohort of MCTD patients and to search for clinical and immunological predictors of this complication presence. Methods: The study included patients, who fulfilled with Alarcon-Segovia and Kasukawa sets of criteria for MCTD. Clinical features of MCTD, autoantibody profile and serum concentrations of IL-1, IL-10, IL-21, IL-23, TNFα, IFNγ, VEGF were assessed. Transthoracic echocardiography (TTE) was performed in all patients to estimate the pulmonary artery pressures. PAH was defined as systolic pulmonary artery pressure (sPAP) ≥36 mmHg according to current guidelines. The study group consisted of 79 patients with MCTD, including 66 (83.5%) women. The median age of patients at the time of the study was 44 years (18-67). Results: 12 patients (15.2%) developed PAH. PAH was statistically significantly more frequent in men, older patients and patients with first MCTD symptoms after 40 years of age. PAH more often developed in patients with BMI>25 and hypertension. The most common serological abnormality, observed in all patients with PAH but only in 51 patients without this complication (100% vs 76%) was the presence of anti-U1-RNP-C antibodies. Among cytokines only reduced serum levels of TNF-α (28, 47 vs 39, 68 pg/ml) correlated with PAH. Patients with high disease activity (ILD, vasculitis, neuropathy, renal involvement, arthritis, serositis, myositis, puffy hands and skin lesions) were more prone to develop PAH than patients with mild disease (14, 75 vs 8, 7). Conclusions: The study showed some clinical correlations of PAH (male gender, BMI >25, hypertension and anti-U1-RNP-C antibodies, low serum levels of TNF-α) that could be useful in defining the patient's profile prone to develop this severe complication. Identifying a subgroup of patients in a risk of development of PAH allows further to applicate early adequate treatment. Acknowledgements: 1 Prakash UBS. Respiratory complication in mixed connective tissue disease. Clin Chest Med 1998;19:733–46. 2 Burdt MA, Hoffman RW, Deutscher SL et al. Long-term outcome in mixed connective tissue disease: longitudinal clinical and serologic findings. Arthritis Rheum 1999;42:899–909. 3 Prakash UBS. Pulmonary manifestations in mixed connective tissue disease. Semin Resp Med 1988;9:318–24. Disclosure of Interest: None declared